Relationship between employee perception of communicative teamwork and selected Herzberg's motivating factors in selected Malaysian organizations - Benrazavi, Seyed Rahim (2011)
This research was conducted to examine the relationship between Job Satisfaction and Communicative Teamwork within a selected number of Malaysian organizations. The study was based on Herzberg’s Motivation-Hygiene theory that explained the relationship between the factors such as Achievement, Recognition, Responsibility, Personal Growth and the Nature of Work with Communicative Teamwork. A survey was conducted on 357 respondents, representing the organizations in the Klang Valley area. A set of questionnaires were used as the instrument for data collection and the gathered data was analyzed through a Multiple Regression test of statistics by means of the Statistical Package for Social Science (SPSS). The study showed the relationship between Job Satisfaction and Communicative Teamwork. This will thus contribute to the process of organizing and other organizational and communication behaviors such as Communicative Teamwork. From the study, it was also found that the indicators of Job Satisfaction namely; Achievement, Recognition, Responsibility, Nature of Work and Personal Growth were positively related to Communicative Teamwork. Thus, suggesting that for a successful practice of Communicative Teamwork, it is essential for any organization to ensure that its members were able to have an understanding of Job Satisfaction in relation with this particular issue. This was shown in the study that the positive perspective of Achievement contributed to Communicative Teamwork. It was also shown that members who gained Recognition in the organization were also motivated in keeping up with practicing Communicative Teamwork. However, although understanding one’s a Responsibility shall contribute to better performance yet this variable did not contribute to Communicative Teamwork of the employees. Nature of Work or the openness and friendliness of the working environment have also shown a significant relationship with Communicative Teamwork, yet the relationship between Personal Growth and Communicative Teamwork was not considerable at all. The study has therefore contributed significantly to the understanding of Herzberg’s Motivation-Hygiene Theory.